2006
DOI: 10.4315/0362-028x-69.9.2241
|View full text |Cite
|
Sign up to set email alerts
|

PCR Identification of Ruminant Tissue in Raw and Heat-Treated Meat Meals

Abstract: To control the spread of bovine spongiform encephalopathy in cattle through contaminated animal feedstuffs, screening of feed products is essential. We designed five pairs of primers to identify specifically raw and heat-treated tissue from cattle, sheep, goat, deer, and ruminants in general. A forward common primer was designed based on a conserved DNA sequence in the mitochondrial 12S rRNA-tRNA(val)-16S rRNA gene, and reverse primers were designed to hybridize with a species-specific DNA sequence for each sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Similarly, Martı´n et al (2007) used the specific primers based on 12S rRNA for identification of four duck species in meat mixtures and specific identification of Muscovy duck even if used on highly damaged DNA. Species-specific primers targeting 12S and 16 rRNA were applied for detection of some animal species like deer and some ruminant animals in meat products by Ha et al (2006). Mule duck was identified by the primer sets of 12S and 5S ribosomal RNA, and a-actin genes (Rodriguez et al 2001(Rodriguez et al , 2003a(Rodriguez et al , 2003b(Rodriguez et al and 2004.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Similarly, Martı´n et al (2007) used the specific primers based on 12S rRNA for identification of four duck species in meat mixtures and specific identification of Muscovy duck even if used on highly damaged DNA. Species-specific primers targeting 12S and 16 rRNA were applied for detection of some animal species like deer and some ruminant animals in meat products by Ha et al (2006). Mule duck was identified by the primer sets of 12S and 5S ribosomal RNA, and a-actin genes (Rodriguez et al 2001(Rodriguez et al , 2003a(Rodriguez et al , 2003b(Rodriguez et al and 2004.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…A minimum detection limit of 0.1% for food products was found in different literatures (Sónia et al, 2010). Ha et al found a minimum detection limit of 0.05% in their experiment (Ha, Jung, Nam, & Moon, 2006). Thus our new method is much more attractive as compared to others due to its minimum detection limit of 0.01% in foodstuffs.…”
Section: Soybeanmentioning
confidence: 61%
“…For some species less represented in literature or whose restriction profiles were ambiguous, the number of samples was increased using whole blood, lymphocytes, and tissues specimens. This type of analysis was preferred to the species-specific PCR assay (Parodi et al 2002;Bottero et al 2003;Steube et al 2003;Dalmasso et al 2004;Gao et al 2004;Myers et al 2004;Martellini et al 2005;Ha et al 2006;Cooper et al 2007;Ono et al 2007), direct sequencing (Hebert et al 2004), and AFLP (Mueller and Wolfenbarger 1999;Milanesi et al 2003), thanks to the fact a8, b8, and c8). In particular, a, b, and c represent, respectively, restriction profiles of the original rat cell line, of the cell line at the fourth passage in culture, and of the cell line at the 27th passage in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Even if standardized systems for isoenzyme characterization are now commercially available, unfortunately, this method still shows several disadvantages: It is not easily reproducible and does not allow for the identification of avian species, and it is expensive and time consuming (in fact, a panel of at least four isoenzymes must be performed to authenticate a single cell line). Other methods can be used to verify the origin of a cell line: immunological and cytogenetic analyses, specific polymerase chain reactions (PCRs; Parodi et al 2002;Bottero et al 2003;Steube et al 2003;Dalmasso et al 2004;Gao et al 2004;Myers et al 2004;Martellini et al 2005;Ha et al 2006;Cooper et al 2007;Ono et al 2007;), amplified fragment length polymorphism (AFLP; Mueller and Wolfenbarger 1999;Milanesi et al 2003), and DNA fingerprinting. This last technique, based on the analysis of polymorphic markers in the genome, is specifically used to find intraspecies cross-contaminants.…”
Section: Introductionmentioning
confidence: 99%